Redefining Islamic Authority in Indonesia: The Dialectics of Pesantren and Tajdid in Contemporary Muslim Society - Muhammad Sairi; Muria Khusnun Nisa; M. Ridwan Lubis (Refleksi: Jurnal Kajian Agama dan Filsafat, 2026)
Existing studies on pesantren and Islamic reform movements have generally examined these traditions separately, while limited attention has been given to their dialogical role in shaping contemporary Islamic authority in Indonesia. This study examines the process of redefining Islamic authority through the interaction between the pesantren tradition and the tajdid movement. Employing qualitative library research with a socio-historical approach, the study analyzes classical and contemporary scholarly works representing both intellectual traditions. The article contributes to the discourse on Islamic authority by positioning pesantren and tajdid as complementary rather than competing traditions. The findings reveal that Islamic authority in Indonesia has evolved through a continuous process of negotiation between tradition and reform. Pesantren preserve scholarly continuity through sanad-based learning, collective deliberation, and contextual adaptation, while the tajdid movement promotes rationalization, purification, and responsiveness to social transformation. Rather than existing in opposition, both traditions contribute to the formation of a dynamic, moderate, and adaptive model of Islamic authority. This study argues that the redefinition of Islamic authority in Indonesia is the result of an ongoing dialogue between traditionalism and reformism, enabling Islamic institutions to respond effectively to contemporary religious, social, and intellectual challenges.